ANALISIS PENGGUNAAN OBAT DI DUA RUMAH SAKIT BERDASARKAN INDIKATOR WHO 1993 - , Inaratul Rizkhy Hanifah., S.Farm, Prof. Dr. Marchaban, DESS., Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Prescribing the rational drugs is the main orientation of the health care activity that should be increase in quality. Since 1985, WHO try to increase the use of rational drug. One of the developing the drugs usage indicator. RSUD Kota City Hospital and PKU Muhammadiyah Hospital are big hospital in Yogyakarta. The research objectiveâs are to analyze of drug use of patient in RSUD Kota Hospital and PKU Muhammadiyah Hospital in the march 2010 period based on WHOâs core indicator and complementary indicator. This research is non-experimental, descriptive design, and prospective data collective. The data are taken in Pharmacy Room in RSUD Kota Hospital and PKU Muhammadiyah Hospital in March 2010 period. Sample are taken in random to 230 samples for both hospital, divide in 1 month or 10 samples per day for each hospital. The results obtained in RSUD Kota hospital are appropriate with standards WHO percentage of encounter with an antibiotic prescribed 21.89%, and injection 0%, while inappropriate the standards is the average drug items used per encounter 2.33, percentage of drugs prescribed by generic name 29.29% and percentage of drugs prescribed from formulary 83.84%. Patient care indicators, the average dispensing time was 17.59 minutes (non-compounded) and 25.67 (compounded), where 94.29% of drugs are dispensed and no one adequately labeled. Health facility indicators, there was formulary availability, and availability of key drugs 100%. WHO complementary indicators in RSUD Kota Hospital that average drug cost per encounter 50914.60 IDR, with 28.95% cost spent on antibiotics and injections of 0%. While the results in PKU Hospital which appropriate with standards WHO percentage of encounter with an antibiotic prescribed 13.35%, and injection 0.62%, while inappropriate standard is average drug items used per encounter of 2.45, percentage of drugs prescribed by generic name 31.99 %, percentage of drugs prescribed from formulary 85.49%. Indicators of average dispensing time is 16.93 minutes (non-compounded) and 31.58 minutes (compounded), where 99.25% of the drugs are dispensed and 82.71% of them adequately labeled. Indicators of health facilities there was formulary availability, and availability of key drugs 100%. WHO complementary indicators, the average drug cost per encounter 106,145.37 IDR, with the cost spent on antibiotics 16.29% and injection 0.50%.